Clinical validation study to measure the performance of the Nerve Root Sedimentation Sign for the diagnosis of lumbar spinal stenosis - Staub, L.; Barz, T.; Melloh, Markus; Lord, S.; Chatfield, M.; Bossuyt, P. (2011)
Lumbar spinal stenosis is a common degenerative disorder of the spine in elderly patients that can be effectively treated with decompression surgery in some patients. Radiological findings in the diagnostic work-up of the patients do not always correlate well with clinical symptoms, and guidance about when to proceed to surgery is inconsistent. The recently described Nerve Root Sedimentation Sign in magnetic resonance scans has been shown to discriminate well between selected patients with and without lumbar spinal stenosis, but the performance of this new test, when used in a broad patient population, is not yet known. We describe the design of a single-centre retrospective chart review to assess the clinical validity of the Sedimentation Sign by evaluating its association with health outcomes in patients with suspected lumbar spinal stenosis. The Sedimentation Sign will be cross-classified with decisions for surgery based on existing tests and patient outcomes in follow-up examinations at 24. months. The results will be used to estimate: i) how well the Sedimentation Sign can distinguish between patients that do or do not benefit from surgery, and ii) the concordance between the Sedimentation Sign and existing tests to explore its possible value as a triage test. This study design will provide data to estimate the potential benefits and harms of using the Sedimentation Sign to guide surgical decisions. The observed proportion of discordant test results will help inform the design of future randomised controlled trials of the Sedimentation Sign. © 2011 Elsevier Inc.